Online Thermodynamics courseware development. (15th September 2008) - Tan, F.L.; Fok, S.C.
This paper presents the development of a web-based courseware to complement and supplement an undergraduate-level course in thermodynamics at Nanyang Technological University (NTU). The courseware is developed and continuously improved by the students, for the students. This on-going process helps to keep the materials updated and adapted to the students' needs. The design considerations, software tools used, and the implementation discussed in this paper may be useful for the advancement of computer-aided instructional tools in other subject areas and institutions.